Будь собой!: роман / сестры Воробей - Воробей Вера (Романы для девочек, 2005)
Экземпляры: ф.2 (2005) / Инвентарный номер: 48734 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 75 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44